Konstitusionalitas Norma Sanksi Pidana sebagai Ultimum Remedium dalam Pembentukan Perundang-undangan - Titis Anindyajati; Irfan Nur Rachman; Anak Agung Dian Onita (Jurnal Konstitusi, 2015)
Intentionally, criminal sanction was seen as an effective solution for the problem of crimes. On the other hand, criminal sanctions also pose as an implementation of state responsibility in maintaining public security, order and legal protection of its citizens. In the development of Indonesian legal system, most of the laws enacted by the state have included criminal sanction in its substance. Therefore, there is a shift in the political law (legal policy) regarding the application of criminal sanctions, which intentionally pose as a last resort (ultimum remedium) has shifted towards first resort (primum remedium). The inclusion of criminal sanctions in the legislation as primum remedium might result on the violation of the constitutional rights of Indonesian citizens. In addition, there is an emergence of numbers in applications  of judicial review on the laws regarding the criminal sanctions issues. This research focuses to examine and determine about the position of criminal sanction norms in the law and about the deliberation and reasoning of the Constitutional Court in reconstructing the structure of criminal sanctions in law from primum remedium toward ultimum remedium. The research showed that most of the laws enacted from 2003 through 2014 have adapted the norms of criminal sanctions as primum remedium. This can be seen in the construction of the criminal forfeiture clause, where in the contrary, the concept of punishment states that criminal sanctions should be positioned as ultimum remedium. In the meantime, the Constitutional Court as the protector of citizens’ constitutional rights and protection of human rights  has  a very important role in  restoring the  position of  criminal  sanctions  as ultimum remedium. This, by example, was set forth in the Constitutional Court decision 4/PUU-V/2007 on June 19, 2007 regarding the review of Law No.29/2004 on the Medical Practices.